Relationship Between Knowledge And Compliance Of Pregnant Women In Consuming Blood Supplement Tablets - Sinaga, Taruli Rohana; Sri Dearmaita Purba; Agnes Purba; Hokkop Perawati Sinaga (Akupun Tour Publisher, 2023)
Purpose : Anemia is the most common and potentially serious public health problem in the world. Groups that are prone to anemia are women of childbearing age and pregnant women. Pregnant women are prone to iron deficiency anemia because the need for oxygen in pregnant women is higher, triggering an increase in erythropoietin production. Because of this, the plasma volume increases and the red blood cells (erythrocytes) increase. Method: The government's efforts to overcome iron deficiency anemia in pregnant women are focused on giving iron tablets to pregnant women. The administration of iron supplement tablets is integrated with the service of visiting pregnant women (antenatal care). The implementation of giving blood-boosting tablets still has many obstacles that are often experienced, one of which is the adherence of pregnant women to taking blood-added tablets as recommended. This research aims to find out the relationship between knowledge and compliance of pregnant women in consuming blood supplement tablets in the working area of the Lontung Health Center. This type of research is analytic with a cross sectional research design. The population in this study was the study population, all pregnant women who had received blood supplement tablets in the working area of the Lontung Health Center, there were 39 people with the total sample in this study being the total population. The data collection method used a questionnaire, and the data was analyzed using the Chi Square test. Results: The results of the study showed that there was a significant relationship between knowledge about blood-supplementing tablets (TTD) and adherence to blood-supplementing tablet consumption in the Lontung Health Center area (p-value = 0.003). Disscusion and Conclusion: In conclusion, knowledge is significantly related to adherence of pregnant women in taking iron tablets in the working area of the Lontung Health Center. when taking blood-boosting tablets and monitoring or monitoring pregnant women when taking blood-boosting tablets.